1995
DOI: 10.3109/00016489509133353
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Threshold and Nasal Mucosal Changes in Experimentally Induced Common Cold

Abstract: Common cold is a most common disease in man accompanied by an experience of a diminished sense of smell. Controlled studies of the sense of smell are lacking and the cause as well as degree of impairment of smell in common cold has not been satisfactorily evaluated. We have investigated whether impaired olfactory ability accompanies common cold and if the loss is related to nasal blockage and to the amount of nasal discharge. For this purpose we measured the threshold of olfaction in volunteers before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
8
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 11 publications
4
63
8
2
Order By: Relevance
“…Nasal congestion has been found to be responsible for olfactory loss and even correlated to objective impairment of nasal patency (111). After treatment of congestion with a corticosteroid an improvement of olfaction was found possibly supporting this assumption (112).…”
Section: Objective Methodssupporting
confidence: 66%
“…Nasal congestion has been found to be responsible for olfactory loss and even correlated to objective impairment of nasal patency (111). After treatment of congestion with a corticosteroid an improvement of olfaction was found possibly supporting this assumption (112).…”
Section: Objective Methodssupporting
confidence: 66%
“…The secretions may prevent the odorous molecules from reaching the receptors in the olfactory epithelium. The findings are somewhat contra dictory to a recent study of the threshold for smell in acute viral rhinitis [8]. In that study, common cold led to impaired smell function, and this effect was correlated with the symptoms of nasal blockage and impaired nasal peak-flow.…”
Section: Discussioncontrasting
confidence: 49%
“…The patient had to decide from which bottle the smell was stronger. The order of presentation was chosen by a com puter and in this manner the threshold was calculated from the per formance during 30 trials [8]. We set the threshold criterion at the concentration of butanol at which the subjects managed to make the right choice in 75% of cases.…”
Section: Olfactory Threshold Testmentioning
confidence: 99%
“…Although only a few studies have quantitatively evaluated olfactory function following viral rhinitis, two have shown olfactory impairment. Akerlund et al [16] found elevated olfactory thresholds to 1-butanol among volunteers who had been inoculated with coronavirus (4 days prior), relative to uninfected control subjects. In this study, the magnitude of olfactory impairment was correlated with the degree of nasal congestion.…”
Section: Olfactory Dysfunction In Rhinitis/rhinosinusitismentioning
confidence: 98%